P96 Access of level 2 sexual health services by men who have sex with men: who goes and what services do they get?. (18th May 2015) - Mebrahtu, Helen; Sile, Bersabeh; Mohammed, Hamish; Were, John; Yung, Mandy; Hughes, Gwenda
Abstract : Background: Men who have sex with men (MSM) bear a disproportionate burden of sexually transmitted infections (STIs) including HIV. While routine STI surveillance data indicate MSM regularly access genitourinary medicine (GUM) services for their sexual health care, the extent to which MSM attend non-specialist Level 2 sexual health services is unclear. We investigated access of Level 2 services by MSM in England. Methods: We used provisional data from the GUM Clinic Activity Dataset (GUMCADv2) to compare the characteristics, service usage and outcomes between MSM accessing GUM and Level 2 services who reported data in 2013. Results: Of all male attendances where sexual orientation was recorded, 12.3% (6, 957/57, 048) of Level 2 attendances were among MSM compared to 26.3% (299, 456/1, 139, 424) of GUM attendances (p < 0.001). MSM attending Level 2 compared to GUM services, were younger (mean age: 30.5 yrs vs 38.5 yrs; p < 0.001), and more likely to be of black ethnicity (6.8% vs 4.1%; p < 0.001) and reside in London (49.9% vs 46.0%; p < 0.001). MSM attending non-GUM services were more likely to have a full sexual health screen (41.4% vs 27.0%; p < 0.001), HIV test (8.9% vs 7.1%; p < 0.001), and be diagnosed with chlamydia (6.2% vs 3.0%; p < 0.001), gonorrhoea (5.6% vs 4.6%: p < 0.001) and first-episode genital warts (1.5% vs 1.0%: p < 0.001). There was no significant difference in the proportion newly diagnosed with HIV (0.57% vs 0.69%; p = 0.268) or first-episode genital herpes (0.47% vs 0.46%; p = 0.830). Conclusion: Level 2 sexual health services play an important role in the sexual health care of MSM, especially those of younger age.